ITEM ANALYSIS OF AN ENGLISH SUMMATIVE TEST - Suek, Leni Amelia (Pattimura University, 2021)
While almost half of the teachers’ activities are assessing their students, they are not well-prepared with assessment literacy training. Hence, they are unable to produce good tests to measure students’ level of knowledge and skills. This study is aimed at analyzing item difficulty and item discrimination of a test made by an English teacher at a junior high school in Kupang. It was descriptive qualitative research and the instruments of the research were test items, answer keys, and students’ answer sheets. For the difficulty index, it was revealed that more than half of the test items were easy, while only 2% of the test items were difficult. In terms of the discrimination index, it was found that only 10% of the test items were excellent and most of the test items (46%) were poor. These findings indicated that the English test had a poor item difficulty index and low item discrimination index. Hence, it did not fulfill the criteria of a good test and could not measure students’ true ability. It is highly recommended for the teachers to improve the test items and for the government to provide assessment training for the teachers so that they can produce good tests.